Evaluation of fungicides for control of bitter and sprinkler rots on apple fruit - Everett, K.R.; Pushparajah, I.P.S.; Taylor, J.T.; Timudo-Torrevilla, O.E.; Spiers, T.M.; Chee, A. Ah; Shaw, P.W.; Wallis, D.R. (New Zealand Plant Protection, 2015)
Bitter rot is an apple fruit disease most commonly caused in New Zealand by the fungus Colletotrichum acutatum The timing of fungicide applications to manage this disease was investigated during two seasons Fungicides applied during October (carbendazim) or November and December (tolyfluanid captan and mancozeb) reduced incidence of rots expressing on trees in the orchard Fungicides (halfstrength copper oxychloride Bacillus subtilis QST 713 and tolyfluanid) applied during January and February reduced the incidence of postharvest rots Bacillus subtilis QST 713 applied regularly throughout the season reduced incidence of field rots but was not effective when the number of applications was reduced Calcium chloride (CaCl2) or copper oxychloride applied during November and December reduced the incidence of sprinkler rots caused by Phytophthora cactorum